Answer:
The change in kinetic energy is zero (0).
Step-by-step explanation:
Given;
mass of the object, m = 3.0 kg
applied force, f = 6 N
distance through the object is moved, d = 4.0 m
The acceleration of the object is calculated as;
f = ma
a = f / m
a = (6) / 3
a = 2 m/s²
The constant speed through which this object is moved is calculated as;
v² = u² + 2ad
v² = 0 + 2 (2)(4)
v² = 16
v = √16
v = 4 m/s
The change in kinetic energy is calculated as;
ΔK.E = K.E(final) - K.E(initial)
ΔK.E = ¹/₂mv₂² - ¹/₂mv₁²
v₂ = v₁ = v (since the mass was moved at a constant speed; v)
ΔK.E = ¹/₂mv² - ¹/₂mv²
ΔK.E = 0
Therefore, the change in kinetic energy is zero (0).